2015
DOI: 10.1093/jxb/erv383
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin perturbation leads to unexpected cell wall modifications and affects stomatal behaviour inPopulus

Abstract: HighlightGrowth-compatible, post-translational modifications of tubulin in transgenic Populus alter cell wall pectin-xylan networks and guard cell movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 82 publications
(116 reference statements)
1
30
0
1
Order By: Relevance
“…In vivo stomatal aperture assays with different microtubule inhibitors indicate that MTs could regulate stomatal function (Fukuda et al , , Huang et al , Marcus et al , Swamy et al , Qu et al ). In the present study, taxol further promoted ALA's effect on microtubule organization and stomatal aperture, while VBT partially inhibited these effects (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo stomatal aperture assays with different microtubule inhibitors indicate that MTs could regulate stomatal function (Fukuda et al , , Huang et al , Marcus et al , Swamy et al , Qu et al ). In the present study, taxol further promoted ALA's effect on microtubule organization and stomatal aperture, while VBT partially inhibited these effects (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MTs in guard cells remain well organized even after differentiation is completely finished, suggesting that MTs may also function in stomatal movement. Fukuda et al (, ), Huang et al (), Marcus et al (), Swamy et al (), and Qu et al () together demonstrated that MTs are indeed required by mature guard cells for stomatal function by in vivo stomatal aperture assays with different microtubule inhibitors. We previously reported the role of ALA in regulating stomatal movement.…”
Section: Introductionmentioning
confidence: 97%
“…The wood samples were ground to pass a 40-mesh screen using a Wiley mill, followed by 99 cycles of ethanol extraction using a Soxhlet extraction unit (Buchi) and air dried. Extractive-free wood meal was used for Klason lignin (Swamy et al, 2015) and crystalline cellulose content determination according to Updegraff (1969). Lignin composition was determined by thioacidolysis (Foster et al, 2010), matrix polysaccharide composition by trifluoroacetic acid hydrolysis (Foster et al, 2010), and glycosyl composition by methanolysis followed by trimethylsilylation (Harding et al, 2018).…”
Section: Matherials and Methodsmentioning
confidence: 99%
“…We then adapted the approach of Liu et al (2016) for construction of sample-specific networks. Briefly, a group of reference samples was assembled from our previous studies unrelated to lignin pathway gene manipulation (Swamy et al, 2015; Xue et al, 2016). Only unstressed xylem samples were included (n=35).…”
Section: Matherials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation